Biodegradation of Pharmaceutical Wastes Using Different Microbial Strains - Kartheek, B. R. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe enormous amount of the pollutants being dumped constantly from the various industries causes severe damages to the environment. Among various components released from different industries, the soluble products like benzene and toluene appears to be more hazardous than other insoluble products present in the wastewater. This hazardous pollutant can be removed by various conventional methods like removal, alteration and isolation of pollutants. However these technologies are more expensive; do not completely destroy rather transforming them form to another. As an alternative, Bioremediation is used to eliminate the above contaminant completely from the environment with very low operation cost. There are many microbial species, which are found to be efficient in the degradation of benzene and toluene. Among those populations, Pseudomonas fluorescence and Bacillus megatherium and fungi such as Aspergillus species, Rhizopus species and Penicillium species were proven to degrade the above pollutants. These organisms were found to grow in the medium supplemented with 100ppm of the benzene and toluene. The results recorded were significant and tolerant.Key words: Pharmaceutical, waste water, benzene, toluene and biodegradation